PRAKTIK SEDEKAH "JUM'AT BERKAH" DALAM PERSPEKTIF SOSIOLOGIS: Sejarah Terciptanya hari Jum'at Berkah, Pengertian Sedekah, Praktik Sedekah Jum'at dalam Perspektif Sosiologis, Dalil-dalil anjuran untuk sedekah di hari Jum'at untuk kehidupan sehari-hari, Manfaat Jum'at berkah dalam Kehidupan Sehari-hari. - MUSYAFA, MUHAMMAD ZAEN (DIALEKTIKA, 2024)
Almsgiving is a noble act of giving something that even though it is of little value but is done sincerely without expecting reciprocity from the recipient. This writing is done with the library research method. This writing will discuss about alms that are done on Friday or what is commonly called jum'at blessing in general and also how the practice of alms “jum'at blessing” is seen in a sociological perspective. The writing of this analysis aims to find out the origin (history) of the blessed Friday which is a special day or sayyidul ayyam (master of the day) in Islam where we are encouraged to do good with a variety of variations including almsgiving, in Indonesia itself the habit of giving alms on Friday is often found in several regions, this culture is not sure who brought it to Indonesia and has developed into a culture in several regions. The benefits of the Friday blessing itself help a lot such as increasing the socialization of the community to ease the burden or economic disparity experienced by some people. This writing also discusses the postulates or recommendations of Islam in giving alms on Friday which has been promised to get a great reward and facilitate their affairs in the world.